Burden of cystic fibrosis in children - Kathryn Bresnick; Emilio Arteaga-Solis; Stefanie J Millar; Glen Laird; Cecile LeCamus (BMJ Open Respiratory Research)
Background Cystic fibrosis (CF) is a genetic, multisystemic, progressive and life-shortening disease caused by mutations in the CF transmembrane conductance regulator (CFTR) gene. Different genotypes have been linked to variations in disease progression among people with CF. The burden of illness (BOI) in children with CF is incompletely characterised, particularly as it relates to CFTR genotypes prior to the availability of the first CFTR modulators. This retrospective, cross-sectional, descriptive study evaluated the BOI in US children with CF <12 years of age prior to the first approval of CFTR modulators.Methods Data from the US Cystic Fibrosis Foundation Patient Registry from 2011 were used to summarise key patient and disease characteristics using descriptive statistics, overall and grouped by age (0 to <2 years, 2 to <6 years and 6 to <12 years) and genotype (F508del/F508del, F508del/minimal function (MF), MF/MF, gating mutation on ≥1 allele, residual function mutation on ≥1 allele and R117H on ≥1 allele) group.Results The analysis included 9185 children. Among 6-year-olds to <12-year-olds, mean (SD) per cent predicted FEV1 in 1 s was 92.6% (17.5%). Among all children <12 years of age, the mean (SD) all-cause hospitalisation and pulmonary exacerbation rates in 2011 were 0.4 (1.0) and 0.3 (0.8), respectively. Most (93.6%) had ≥1 positive lung microbiology culture. CF-related medication and nutritional supplementation use was common across all ages and genotypes. More than half (54.7%) had ≥1 CF-related complication. Evidence of disease burden was observed across the age and genotype groups studied.Conclusions Prior to the approval of the first CFTR modulator therapies in children <12 years of age, CF was associated with substantial BOI from an early age—including respiratory infections, hospitalisations/pulmonary exacerbations, need for supplemental nutrition and pharmacological treatments—irrespective of genotype.